TRIPURI MEITE IS IN NATIONALIZATION OF MANIPURI DANCE: AN APPRAISAL OF THEIR CONTRIBUTIONS - P., Lilabati Devi; Devi, Soibam Priyadarshini (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Manipur, a far northeastern state of India is known for its rich cultural heritage, prominently manifested in its performing arts. Among the performing art forms of Manipur, Manipuri Dance is regarded and well known nationally and internationally as one of the classical dances of India. It is of great importance that the great poet of India, Rabindranath Tagore institutionalized Manipuri Dance in Santiniketan and paved its way to nationalization of the dance form. And even more, of great significance, that it is the Manipuri Diasporic Community of Tripura that showcased its platform as a dance form of rich heritage and of Manipuri cultural embodiments. So far, little research and study have been done regarding the contributions of Manipuri diaspora community in Tripura and their role in the propagation of Manipuri Dance. The paper is a humble study on the contributions of Manipuri Diaspora, notably the Manipuri Queens in Tripuri Royal citadel, aid of Tripuri kings in providing the platform which culminates into popularizing it beyond the kingdom, through the efforts of Rabindranath Tagore.